WATER BUG Diplonychus rusticus (HEMIPTERA: BELOSTOMATIDAE) AS A BIOCONTROL AGENT FOR CULEX MOSQUITO - VASSOU, MIRIAM CECILIA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Belostomatid water bugs have been reported to be highly predaceous on mosquito larvae, and have been reported to kill and suck the content of the mosquito larvae. The present study aims at determining the predatory efficiency of Diplonychus rusticus as an efficient bioagent on Culex larvae. 275 adult water bugs were introduced into a pond containing 275 liters (±10%) of water. 27,500 Culex larvae were added. At the end of 6 hours and 24 hours the number of live larvae were collected and were noted. The results of this study proved the importance of water bug in the anti-mosquito management.